Do the comments we receive on our performance change our motivation? A look at how feedback affects our level of motivation to complete a task. - Schroeder, Alexis (East Carolina University, 2022)
Motivation is a key aspect of day-to-day life. We know that internally motivated individuals are not affected by rewards given from low-interest tasks (Eisenberg, 1999). The purpose of this study was to pilot our motivation survey and to understand how an individual’s type of motivation; internal, external, or amotivated, affects motivation level changes due to feedback. The online study involved 65 participants completing a reaction time task. Before the task, the participants completed a questionnaire asking them about their level of motivation from 0 (not motivated at all) to 100 (completely motivated), and their type of motivation (do they complete tasks like these because they are fun, because they would feel ashamed if they quit, etc.). The task required participants to respond as fast as possible by hitting a key on their keyboard corresponding to the placement of the ball on the screen. Upon completing the task, participants received bogus feedback and answered the same motivation survey. We hypothesized that individuals who are internally motivated will be highly motivated whether they’re told they are performing well or not, those who are externally motivated (more affected by the feedback they receive) will be less motivated if they are told they are doing bad and more motivated if they are told they are doing well, and those who are amotivated will remain amotivated. Results indicated that participants who were internally motivated (n=42) and were given feedback that they were in the 93rd percentile (n=21) had on average a starting motivation of 77 and an average motivation level of 85 after having received the bogus feedback. The participants that were internally motivated and were told they were preforming in the 37th percentile (n=21) had an average starting motivation of 79 and an average motivation level of 79 after having received the bogus feedback. Externally motivated participants (n=6) and amotivated participants (n=3) had trends consistent with those seen in the internally motivated participants; this is unexpected but can be explained by the low number of participants. These findings are consistent with the hypothesis concerning intrinsically motivated individuals; more participants would be needed in order to analyze the results of externally and amotivated individuals. This study is continuing with the goal being to create and pilot a pair version.
Keywords: Motivation, feedback, reaction time task